Scientometric analysis of the advances, challenges, and perspectives of Photovoltaic/Thermal (PV/T) systems - Almanza Quispe, Williams Sergio (2025)
Population growth and urbanization generated a greater global energy demand, positioning solar energy as one of the main sustainable alternatives to address this challenge. The aim of this study was to map the advances, challenges, and perspectives of photovoltaic-thermal (PV/T) systems through a bibliometric analysis and a review of the most relevant publications from the Scopus database. Applying predefined inclusion and exclusion criteria, a total of 1077 documents were processed using Biblioshiny, an R-based interface, and VosViewer. The countries with the highest scientific production and international collaboration were China, India, and Iran, with the University of Science and Technology of China standing out as the most influential institution. The most prominent journal was Solar Energy, based in the United Kingdom. The most frequently cited studies highlight significant advances in inorganic, organic, and nanomaterial-based technologies aimed at improving conversion efficiency and overall system performance. Nevertheless, challenges persist regarding the economic and technical integration of these systems across diverse climatic and geographic contexts. Additionally, the importance of developing hybrid technologies is emphasized, combining artificial intelligence and machine learning techniques with circular economy principles to achieve greater efficiency, along with policies that support research and large-scale implementation of these systems.